2002
DOI: 10.1046/j.1365-2958.2002.03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene required for the biosynthesis of ornithine‐derived lipids

Abstract: Summary Phospholipids are the membrane‐forming constituents in all living organisms. In addition to phosphorus‐containing lipids, the membranes of numerous bacteria contain significant amounts of phosphorus‐free polar lipids, often derived from amino acids. Although lipids derived from the amino acid ornithine are widespread among bacteria, their biosynthesis is unknown. Here, we describe the isolation of mutants of Sinorhizobium meliloti deficient in the biosynthesis of ornithine‐derived lipids (OL). Compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 51 publications
3
101
0
Order By: Relevance
“…The second step of ornithine lipid biosynthesis is catalyzed by the protein product of olsA (Fig. S1), which is frequently found downstream of olsB (30,31). Unexpectedly, the amino acid sequence of HTCC7211_00011010 did not cluster with OlsA sequences from characterized enzymes, despite all three having phospholipid/glycerol acyltransferase domain (IPR002123) signatures.…”
Section: Resultsmentioning
confidence: 97%
“…The second step of ornithine lipid biosynthesis is catalyzed by the protein product of olsA (Fig. S1), which is frequently found downstream of olsB (30,31). Unexpectedly, the amino acid sequence of HTCC7211_00011010 did not cluster with OlsA sequences from characterized enzymes, despite all three having phospholipid/glycerol acyltransferase domain (IPR002123) signatures.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, inactivation of PA4351 does not affect the fatty acid composition of the membrane (data not shown), suggesting that LptA is the main LPA acyltransferase in P. aeruginosa PAO1. The phosphate-starvation-induced PA4351 gene (Lewenza et al, 2005) encodes a protein with 50 % similarity to the OlsA acyltransferase involved in ornithine lipid synthesis in Sinorhizobium meliloti (Weissenmayer et al, 2002). It has been suggested that the present group of 'lysophosphatidic acid acyltransferases' encompasses numerous subgroups with slightly different and overlapping biochemical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Genes predicted to be involved in OL synthesis can be found in 50% of the sequenced bacterial species (1) but have not been described in eukaryotes or archaea (2,3). An OL synthesis pathway was discovered first in the ␣-proteobacterium Sinorhizobium meliloti (4,5). The N-acyltransferase OlsB transfers a 3-hydroxy fatty acyl residue from the constitutive acyl carrier protein AcpP to the ␣-amino group of ornithine forming lysoornithine lipid (4).…”
mentioning
confidence: 99%
“…The N-acyltransferase OlsB transfers a 3-hydroxy fatty acyl residue from the constitutive acyl carrier protein AcpP to the ␣-amino group of ornithine forming lysoornithine lipid (4). Then the O-acyltransferase OlsA transfers a fatty acyl residue from AcpP to the lyso-ornithine lipid, thereby yielding OL (5). Recently, the OL synthase OlsF was described in Serratia proteamaculans (1).…”
mentioning
confidence: 99%